Living in Sawah-Sawah: Between the cheapness of land and the expensiveness of peacefulness - Adinda, Keyrina; Basir, Muhammad (Glocal Society Journal, 2025)
The Tallo Riverbank is an area with a high potential for flooding. Even so, some community groups continue to survive and make the area their settlement, one of which is in the RT 3/RW 7 area, Antang Village, Manggala Subdistrict, Makassar City. This study aims to understand the community's views on flooding, the risks they face and perceive, as well as the practices undertaken in dealing with flood risks. Using a qualitative approach, this research explores the experiences and views of the community directly to gain a more comprehensive understanding of the community's struggle with flooding. Data collection techniques used were observation and in-depth interviews. This study involved 10 informants, which included 5 men and 5 women. This research shows that the community of RT 3/RW 7 faces various risks due to flooding, ranging from safety risks, economic risks, and health risks. However, economic limitations, proximity to livelihood sources and access to education, as well as strong social ties with the local community influence the perception of flood risks. Thus, the decision to live in flood-prone areas is not just a natural hazard with high risks, but part of daily life that must be faced by developing various practices to respond to flood risks ranging from mitigation, evacuation, to recovery. The results of this study are expected to be a reference for practical implementation through the development of community-based flood mitigation pilot projects.